2008
DOI: 10.1007/s10457-008-9113-x
|View full text |Cite
|
Sign up to set email alerts
|

Contour hedgerow intercropping in the mountains of China: a review

Abstract: Hedgerow intercropping systems were introduced in China in early 1990s. Achievements in research and extension of contour hedgerow intercropping in China during the past 15 years are reviewed here. Results reported in over 70 published papers have shown that hedgerow intercropping contributes to soil and water conservation, soil fertility amelioration, land productivity improvement, bioterrace formation, and gives more options for income generation based on local resources in mountain areas. Research and demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Contour planting of trees has also proved successful in limiting runoff and erosion and improving fertility on hillslopes under a wide range of climatic conditions in China (Sun et al 2008). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Contour planting of trees has also proved successful in limiting runoff and erosion and improving fertility on hillslopes under a wide range of climatic conditions in China (Sun et al 2008). …”
mentioning
confidence: 99%
“…However, agroforestry does not always provide a solution, as negative interactions may occur due to competition with adjacent crops (Ong et al 2006(Ong et al , 2007Sun et al 2008). Some reports suggest there is little competition on bench terraces due to spatial or temporal separation of the trees and crops (Cooper et al 1996), although farmers have reported that trees may compete with adjacent crops (Wajja-Musukwe et al 1997;Sun et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crops are produced in the alley-like spaces between the hedgerows (Sun et al 2008). Hedgerows can reduce the generation of runoff, and can intercept eroded sediments from the upper slopes so that soil fertility can be conserved (Lal 1989a).…”
Section: Introductionmentioning
confidence: 99%
“…Shen (1998) and Zhao et al (2004) reported that bio-terraces can form on 15-25°slopes after 4-7 years by planting hedgerows. The cost of bio-terraces is only 3-17% of that of engineered terraces, and they are also much more stable (Sun et al 2008). However, due to the limited soil depth in the Three Gorges Area, this type of terrace is often associated with high spatial variability in soil fertility and crop responses.…”
Section: Introductionmentioning
confidence: 99%